Equal long-term care for equal needs with universal and comprehensive coverage? An assessment using Dutch administrative data - Marianne Tenand; Pieter Bakx; Eddy Van Doorslaer (Tinbergen Institute, 2018)
The Netherlands is one of the few countries that offer generous universal coverage of long-term care (LTC). Does this ensure that the Dutch elderly with similar care needs receive similar LTC, irrespective of their income? In contrast with previous studies of inequity in care use that relied on a statistically derived variable of needs, our paper exploits a readily available, administrative measure of LTC needs, stemming from the eligibility assessment organized by the Dutch LTC assessment agency. Using exhaustive administrative register data on 616,934 individuals aged 60 and older eligible for public LTC, we find a substantial pro-poor concentration of LTC use that is only partially explained by poorer individuals' greater needs. Among those eligible for institutional care, higher-income individuals are more likely to use – less costly – home care. This pattern may be explained by differences in preferences, but also by their higher copayments for nursing homes and by greater feasibility of home-based LTC arrangements for richer elderly. At face value, our findings suggest that the Dutch LTC insurance `overshoots' its target to ensure that LTC is accessible to poorer elderly. Yet, the implications depend on the origins of the difference and one's normative stance.
Keywords: J14; I14; D63; 330; Long-term care; Equity in care use; Horizontal equity; Socio-economic inequality